Z-6=z-4

Simple and best practice solution for Z-6=z-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Z-6=z-4 equation:


Simplifying
Z + -6 = z + -4

Reorder the terms:
-6 + Z = z + -4

Reorder the terms:
-6 + Z = -4 + z

Solving
-6 + Z = -4 + z

Solving for variable 'Z'.

Move all terms containing Z to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + Z = -4 + 6 + z

Combine like terms: -6 + 6 = 0
0 + Z = -4 + 6 + z
Z = -4 + 6 + z

Combine like terms: -4 + 6 = 2
Z = 2 + z

Simplifying
Z = 2 + z

See similar equations:

| -2x-7=32 | | (4+8)n=36 | | (4+8)n=3 | | 10x-14=-2x-13 | | 772x= | | 10x-14=2x+13 | | 5y+39+4x+6=180 | | x(x+2)=1295 | | 9x-15=-5x-16 | | 9x-15=5x+16 | | n-8+3=5 | | 8x+2=4(6x-9) | | 26=2x-8+4x | | 8x+2=4-(6x-9) | | .6(X+100)+.8X=109 | | 104=2x+2(x+4) | | .2x+7.9=6.6 | | 60-5x=6 | | 6x+9y+5x+2y= | | -2x+3=4x-1 | | 10c^2+8c+12=-9 | | (-3)+17-6(-3)=2 | | (3x/3)=90 | | 5(8x-5)+7=32 | | 4590=40t^4+1560t^2 | | 10c+8c+12=-9 | | .17y+.04(y+8000)=2000 | | 8e^7x=1632 | | (X+15)(x-3)=0 | | -.7=0.2x | | -8x-x^2+63=0 | | 2x+2-1-x-2=2 |

Equations solver categories